Small Bowel Ischemic Necrosis Secondary to Idiopathic Intimal and Medial Hyperplasia of Mesenteric Vessels: A Case Report - Sharma, MD, Meenal; Zhou, MD, PhD, Zhongren (North American Journal of Medicine and Science, 2017)
Small bowel ischemic necrosis secondary to idiopathic intimal and medial hyperplasia of mesenteric small vessels is rare. The mesenteric vascular diseases were recently classified as two vascular diseases: fibromuscular dysplasia (FMD) of artery and mesenteric arteriovenous dysplasia/vasculopathy (MAVD/V). FMD usually involves medium size mesenteric arteries in younger individuals. In contrast, MAVD/V tends to affect multiple small mesenteric arteries and veins without vascular lesions in other organs. We reported that a 54-year-old female presented to emergency room with acute onset abdominal pain, nausea and vomiting. CT angiography showed “string of beads” in mesenteric vessels, but did not reveal any vascular narrowing elsewhere in the full body scan. The patient had small bowel ischemic necrosis secondary to idiopathic intimal and medial concentric smooth muscle hyperplasia in mesenteric vessels. The overall picture is consistent with MAVD/V. [N A J Med Sci. 2017;10(1):25-28. DOI: 10.7156/najms.2017.1001025]